Social adaptation- influencing factors- methods of treatment (A study in the context of the Syrian educational reality) - البيرق علي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study examines the problems of social adaptation that children face in the school environment. The transition to a new school environment brings many challenges for children, such as establishing social connections, managing relationships with peers, adapting to unfamiliar social dynamics. Social counseling approaches recognize the importance of social and family factors in the child’s adaptation process and provide specific support for the development of the child’s social skills, emotional intelligence, communication skills and the ability to understand social situations. This research focuses on the main theoretical elements of the social counseling approach, including creating a safe and supportive environment through communication with families, promoting self-awareness and empathy, and developing effective communication and conflict resolution skills. The research also highlights the interaction of the social counseling approach with the child’s personal characteristics, the characteristics of the family environment and life history, and indicates that each child is unique and factors such as introversion, extraversion, self-esteem and social skills can be taken into account to address specific challenges and build on each child’s strengths. Emphasizing the need for social and psychological counselors who can adapt interventions to suit each child in general, this research highlights the fundamental role of the social counseling approach in addressing the problem of social adaptation of children in schools. By focusing on the development of social skills, emotional competence and inclusion, a positive and collaborative school environment can be created that is conducive to children’s overall growth and success.